Cross‐sectional survey of cattle haemopathogens in Constantine, Northeast Algeria. Issue 4 (8th March 2021) - Foughali, Asma Amina; Ziam, Hocine; Aiza, Asma; Boulkrout, Halima; Berber, Ali; Bitam, Idir; Gharbi, Mohamed
Abstract: This aim of the present study was to estimate the prevalence of haemopathogens in cattle in Beni Hamidene locality, district of Constantine (Νortheastern Algeria). Between June and October 2014, 169 bovines from 25 farms were included in this survey, 32 (18.9%) among them were suspected of piroplasmosis and/or anaplasmosis. Infection prevalences were estimated by microscopic examination of Giemsa‐stained blood smears and blood samples from all included cattle ( n = 169). Animals were infected by Theileria annulata (65/169; 38.46%), Anaplasma marginale (22/169; 13%) and Babesia bovis (5/169; 3%). Two co‐infection patterns were found: Theileria annulata/Anaplasma marginale (7.69%) and Theileria annulata/Babesia bovis (1.18%). Only one farm had no cattle infected by any of the haemopathogens. There was a signification difference of T. annulata infection prevalence according to age category ( p =.04). These results emphasised mainly the presence of bovine tropical theileriosis in northeastern, Beni Hamidene locality, province of Constantine, Algeria. Abstract : This aim of the present study was to estimate the prevalence of haemopathogens in cattle in Beni Hamidene locality, district of Constantine (eastern Algeria)